GIFTEDNESS AND GIFTED EDUCATION (AN OVERVIEW) - Azhari, Teuku (LET: Linguistics, Literature and English Teaching Journal, 2013)
Aceh has great talents and prodigy who need intervention. Talking about these talents should start with understanding them as a whole, who they really are, how can we identify them, how can we best serve them for their best potential growth.  Designing the programs that best suit them become the next step after carefully selecting them. Later, we need to formulate special programs, special schools, special human resource who will work with them to boost these prodigies? abilities. Failing to do so will only result in undermining and downgrading their ability instead of doing them a favor. It is highly recommended that government start tapping into this as early as possible for maximum result. In this short article, I also present on how government should work with these talents and prodigies by carefully selecting them. Selection process will later base the whole programs and determine its success. Different approach and interventions are presented here as option and ways to be taken and considered for best result possible.  These approaches are not the only solution to be considered. There should be more out there that government should also consider. Last aspect, but not least, is developing human resources who will teach them. Teachers must be carefully selected and trained so that they can understand and are able to pace up and formulate the curriculum that best serve their students? need.